PELATIHAN PEMBUATAN KOMPOS DARI LIMBAH PERTANIAN DI KAMPUNG ANUMBOB DISTRIK KURIK KABUPATEN MERAUKE - Mangera, Yosefina; Fachriza, Riza; Jamaludin, Jamaludin; Wahida, Wahida; Malesi, Waode Asryanti Wida (Musamus University, 2023)
Merauke Regency is an area where most of the people work as farmers. Rice commodity is the most widely cultivated commodity by farmers besides vegetables and fruits. Farmers' cultivation practices are still using inorganic/chemical fertilizers to meet nutrient needs. The very high demand for inorganic fertilizers is not followed by their timely availability whenever needed, besides that the market price is quite expensive so that production costs increase. This encourages the use of crop residues in the form of husks as raw material for making compost and livestock manure. Burning rice husks produces husk charcoal containing various nutrients as well as cow dung. The purpose of this community service activity is to provide training on making compost from a mixture of charcoal husks, bran, cow dung and EM-4 to farming communities, village officials, Gapoktan, high school and agricultural vocational high school students. This activity was carried out in stages starting from field observations, provision of materials, training/practice on making compost in Anumbob Village, monitoring and teaching how to pack, label and apply compost to the soil. The combination of rice husk charcoal and cow dung as raw material for compost is able to maintain soil moisture and provide nutrients, improve soil conditions on land with low availability of nutrients and water. In addition, we hope that with this training, agricultural waste that was previously not used can have added value, especially by turning it into compost which is useful for reducing agricultural waste, fertility of agricultural land, and ensuring the sustainability of agriculture in the future.